03 Back to basics—ECG impedance analysis for CPR quality control and feedback after out-of-hospital cardiac arrest: a pilot study. Issue 3 (1st March 2011) - Lyon, Richard; Gowens, Paul; Egan, Gerry; Andrews, Peter; Clegg, Gareth
Abstract : Background: Out-of-hospital cardiac arrest (OHCA) remains a leading cause of mortality and severe neurological disability. Survival from OHCA depends on good quality cardiopulmonary resuscitation from EMS personnel. The 'time on the chest' and interruption time for defibrillation have recently been shown to be pivotal to survival. Electrocardiograph impedance analysis software allows retrospective quality control and feedback to EMS crews after a resuscitation attempt. Whilst this technique has been used by several EMS services worldwide, routine use and acceptance has yet to be established. Aims: To establish the feasibility of using impedance software for pre-hospital resuscitation quality control and to gain baseline data on pre-hospital resuscitation practice in the Lothians region of Scotland. Methods: Prospective, observational pilot study. After a resuscitation attempt the attending EMS crew was asked to consent to the ECG trace from the defibrillator being downloaded onto a research computer. The impedance trace was then analysed using computer software (Codestat – Physio Control) and a report on the resuscitation attempt generated. Results: 9 OHCA were included in the pilot. All EMS crews agreed to the download from the defibrillator and all found viewing the trace informative. Downloading the ECG trace was straightforward in all cases. The mean time of the resuscitation attempt spent performing chest compressions was 50%. The mean chest compression rate was 141 min. The mean time from cessation of chest compressions to delivery of defibrillatory shock was 46 s. Conclusion: ECG impedance analysis is a straightforward, accurate, accepted method of assessing quality of pre-hospital resuscitation by EMS personnel. Baseline data from our region suggests that the quality of advanced life support could be improved by focussing on basic elements of resuscitation. Using software-generated resuscitation reports could be useful for EMS personnel feedback and monitoring effectiveness of training programmes. Further research is warranted on the widespread use of this technique.